MODIFIKASI PELAT PENAHAN ALAT PENCETAK HIDROLIK UNTUK MENINGKATKAN KUALITAS BRIKET KULIT ASAM - Seran, Klemens Yansen; Dethan , Jemmy J. S.; Koehuan, Jonathan E. (Tahta Media Group, 2025)
This study aimed to evaluate the effect of modifying a hydraulic briquette press by adding a retaining plate to the molding cylinder on machine performance and the physical–mechanical quality of tamarind shell briquettes. The research was conducted experimentally by comparing the performance of the press before and after modification. The observed parameters included compaction pressure, briquette weight, production efficiency, dimensions, and compressive strength. The results showed that the addition of the retaining plate increased the compaction pressure from 60 kg/m² to 120 kg/m². Briquette weight increased from 50.75 g to 54.75 g, while production efficiency improved from 65.86% to 67.57%. The compressive strength of the briquettes also increased from 26.5 kg/m² to 31 kg/m². The improvement indicates that the retaining plate enhanced force transmission efficiency and created a confined compaction condition, resulting in a denser internal structure and better mechanical resistance. Overall, this simple structural modification effectively improved briquette quality without increasing the jack capacity and can be applied as an appropriate technology for laboratory and small-scale production systems.